2018
DOI: 10.15666/aeer/1605_72717287
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low Temperatures on Enzyme Activity, Chlorophyll and Ion Contents in Common Bean Genotypes

Abstract: Low temperatures slow down plant growth and development and generate physiological damages on plants. Metabolism of largely produced and consumed common bean (Phaseolus vulgaris L.) plants decelerates at temperatures below 15 °C. This study was carried out at Van Yuzuncu Yil University in Van province of Turkey with limited vegetation period due to its cold climate in winter. In this study, the bean plants were subjected to low temperature stress and catalase (CAT), super oxide dismutase (SOD), ascorbate perox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…Bu nedenle kuraklık, tarımsal üretim için en önemli sınırlayıcı faktörler arasında yer almaktadır (Liu ve Stützel, 2004;Özfidaner vd., 2018). Abiyotik streslerde reaktif oksijen türlerinin (ROS), bitkilerde strese karşı toleransın artırılmasında önemli rol oynadığı düşünülmektedir (Kabay 2018a;Kabay 2018b). Kuraklık stresi bitkilerde enzim aktivitesi ve enzim miktarı üzerine de önemli bir etki yapar.…”
Section: Introductionunclassified
“…Bu nedenle kuraklık, tarımsal üretim için en önemli sınırlayıcı faktörler arasında yer almaktadır (Liu ve Stützel, 2004;Özfidaner vd., 2018). Abiyotik streslerde reaktif oksijen türlerinin (ROS), bitkilerde strese karşı toleransın artırılmasında önemli rol oynadığı düşünülmektedir (Kabay 2018a;Kabay 2018b). Kuraklık stresi bitkilerde enzim aktivitesi ve enzim miktarı üzerine de önemli bir etki yapar.…”
Section: Introductionunclassified
“…Similarly, previous study also found that there were greater decrease of chlorophyll a and b contents in low temperature sensitive common bean genotype than in tolerant one. 43 This indicates that the photosynthetic system of T722 suffered minor damage. Chlorophyll fluorescence emission is a noninvasive, effective, and reliable technique for detecting photosystem II (PSII) damage in plants exposed to abiotic stress environment.…”
Section: Discussionmentioning
confidence: 95%
“…Excessive ROS content in plant cells will destroy the ROS balance mechanism [ 8 , 9 ], but they will remove harmful H 2 O 2 and O 2 − from plants through the circulation of superoxide dismutase (SOD), peroxidase (POD), catalase (CAT) enzyme systems, and glutathione–ascorbic acid (GSH–AsA) [ 10 ]. Low-temperature stress on beans will affect the yield, quality, and metabolic rate of kidney beans [ 11 ]. There are two stages of sensitivity to low temperature: the first is the seedling stage [ 12 ] and the second is the flowering stage.…”
Section: Introductionmentioning
confidence: 99%